The contribution of self‐disclosure to promotional response: Examining the roles of deservingness and social class - Wang, Jun; Han, Bing; Liu, Yi (Psychology & marketing, 2023)
Facing the fact of declining sales of firms, promotions serve as an important tool to facilitate short‐term sales. Yet, marketers still face the question of promotion effectiveness based on consumer self‐disclosure behavior. In this paper, we examine the effects of self‐relevant information disclosure on promotional response as well as the mechanism and boundary conditions associated with this effect. Four studies using both real and fictitious brands across a variety of contexts were conducted to test the hypotheses and show that self‐disclosure contributes to promotional response because of the enhanced feeling of deservingness. Moreover, this research also demonstrates that self‐disclosed consumers from a lower social class are more likely to respond to promotions. Taken together, these insights contribute to the research on promotions and self‐disclosure and can be helpful to marketers by suggesting some guidelines for developing cost‐effective promotion strategies, for example, identifying the target consumer segments for promotions.